1982
DOI: 10.1007/bf00056778
|View full text |Cite
|
Sign up to set email alerts
|

Studies of esterase 6 in Drosophila melanogaster XII. Evidence for temperature selection of Est 6 and Adh alleles

Abstract: Changes in allele frequencies at the esterase 6 (Est 6) and alcohol dehydrogenase (Adh) enzyme loci of Drosophila melanogaster and simulans are examined in natural populations and artificial populations maintained at two temperatures. Results from cage populations at 18 °C and 25 °C provide evidence for temperature selection at both loci. Seasonal population samples show no significant change in gene frequencies for either locus, a reasonable outcome given the small selection coefficients found in cage populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…It has by now become evident that the Est-6 polymorphism has an adaptive significance based either on its already demonstrated involvement in the reproductive process (Gilbert and Richmond, 1982) or on its role in the metabolism of esters (Zera et a!., 1983;Costa et a!., 1985). The results reported here together with the other findings for outbred and inbred populations cited above, suggest however that the Est-6 locus is not only involved in selective processes per se but also because of its interactions with other loci.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…It has by now become evident that the Est-6 polymorphism has an adaptive significance based either on its already demonstrated involvement in the reproductive process (Gilbert and Richmond, 1982) or on its role in the metabolism of esters (Zera et a!., 1983;Costa et a!., 1985). The results reported here together with the other findings for outbred and inbred populations cited above, suggest however that the Est-6 locus is not only involved in selective processes per se but also because of its interactions with other loci.…”
Section: Discussioncontrasting
confidence: 48%
“…It seems worth considering the hypothesis that this interaction is due to a difference in the pattern of oviposition among genotypes. Previous results (Gilbert and Richmond, 1982) have suggested that male Est-6 promotes ejaculate transfer, sperm storage and use in females. A quantitative study of sperm use during the first 50 hours after mating by using Est-6 null and active stocks of Drosophila melanogaster (Gilbert et a!., 1981) demonstrated that the rate of sperm release is related to the level of Esterase-6 activity suggesting the involvement of this enzyme, present in the seminal fluid, in sperm motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of methylmalonate, we suggest that the selective action could be caused by a cleavage product of the substrate (malonate) which is a powerful inhibitor of succinate dehydrogenase, and should have a negative effect on respiration. Sexual selection (Gilbert and Richmond, 1982) through allozymic differences in reproductive functions such as sperm use and mating and remating behaviour, has been demonstrated to be one of the most likely mechanisms responsible for the maintenance of the Est-6 polymorphism. Our results, concerning laboratory populations set up with forced matings, indicate that the catalytic function(s) of Esterase-6 in ester metabolism can also be a target of selection.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has been studied in laboratory populations with a variety of approaches by many workers. Evidence for selection mainly dependent on frequency, temperature and density, and involving the chromosomal regions carrying genetic variability for the Est-6 locus has been produced (Maclntyre and Wright, 1966;Kojima and Yarbrough, 1967;Birley and Beardmore, 1977;Costa and Beardmore, 1980;Gilbert and Richmond, 1982). Moreover, it has recently been demonstrated that the Esterase-6 allozymes are involved in reproductive processes (Richmond et al, 1980); Esterase-6 seems to influence female productivity and the timing of subsequent remating (Gilbert, Richmond and Sheehan, l98la, b;Gilbert and Richmond, 1981;Richmond and Senior, 1981).…”
Section: Introductionmentioning
confidence: 99%